Guns, Environment, and Abortion: How Single-Minded Voters Shape Politicians' Decisions - Laurent Bouton; Paola Conconi; Francisco Pino; Maurizio Zanardi (Center for Economic Studies and ifo Institute (CESifo), 2018)
We study how electoral incentives affect policy choices on secondary issues, which only minorities of voters care intensely about. We develop a model in which office and policy motivated politicians choose to support or oppose regulations on these issues. We derive conditions under which politicians flip-flop, voting according to their policy preferences at the beginning of their terms, but in line with the preferences of single-issue minorities as they approach re-election. To assess the evidence, we study U.S. senators' votes on gun control, environment, and reproductive rights. In line with our model's predictions, election proximity has a pro-gun effect on Democratic senators and a pro-environment effect on Republican senators. These effects only arise for non-retiring senators, who represent states where the single-issue minority is of intermediate size. Also in line with our theory, election proximity has no impact on senators' decisions on reproductive rights, because of the presence of single-issue minorities on both sides.
Keywords: D72; I18; K38; Q00; 330; electoral incentives; environment; gun control; reproductive rights